2009
DOI: 10.1523/jneurosci.3158-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

CD14 and Toll-Like Receptors 2 and 4 Are Required for Fibrillar Aβ-Stimulated Microglial Activation

Abstract: Microglia are the brain's tissue macrophages and are found in an activated state surrounding ␤-amyloid plaques in the Alzheimer's disease brain. Microglia interact with fibrillar ␤-amyloid (fA␤) through an ensemble of surface receptors composed of the ␣ 6 ␤ 1 integrin, CD36, CD47, and the class A scavenger receptor. These receptors act in concert to initiate intracellular signaling cascades and phenotypic activation of these cells. However, it is unclear how engagement of this receptor complex is linked to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
424
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 509 publications
(445 citation statements)
references
References 109 publications
21
424
0
Order By: Relevance
“…We found that activation of TLR2 serves as a critical trigger for hIAPP-induced Il1b expression in both BMDMs and cultured islets. Interestingly, diverse amyloidogenic peptides appear to act as endogenous ligands for TLR2: activation of TLR1/2 has been described for A␤ (32,33), serum amyloid A (34), lysozyme fibrils (12), curli fibrils (11), and ␣-synuclein (35). Lysozyme may also activate TLR2/6 (12), and our data suggest that heterodimerization with TLR6 is required for sensing of IAPP by TLR2.…”
Section: Discussionsupporting
confidence: 53%
“…We found that activation of TLR2 serves as a critical trigger for hIAPP-induced Il1b expression in both BMDMs and cultured islets. Interestingly, diverse amyloidogenic peptides appear to act as endogenous ligands for TLR2: activation of TLR1/2 has been described for A␤ (32,33), serum amyloid A (34), lysozyme fibrils (12), curli fibrils (11), and ␣-synuclein (35). Lysozyme may also activate TLR2/6 (12), and our data suggest that heterodimerization with TLR6 is required for sensing of IAPP by TLR2.…”
Section: Discussionsupporting
confidence: 53%
“…Phagocytosis is one of the key mechanisms for microgliamediated fibrillar and oligomeric Aβ removal [22,41,50,[64][65][66][67]. Large particles like fAβ are taken up by phagocytosis through engagement of innate immune surface receptors and activation of the cell's phagocytic machinery.…”
Section: Phagocytosismentioning
confidence: 99%
“…Further evidence suggesting a role for TLRs in microglial responses to Aβ was provided in a study where microglia derived from TLR2, 4 and CD14 KO mice were defective in Src-Vav-Rac and p38 MAPK signalling and showed reduced ROS production and phagocytosis in response to FAβ [39]. This suggests that TLR2, TLR4 and CD-14 are part of the receptor complex that responds to FAβ.…”
mentioning
confidence: 97%
“…a physical interaction between CD14 and fibrillar Aβ (FAβ) was demonstated by Reed Geaghan et al [39]. The signal transduction cascades triggered by FAβ is identical to those triggered by TLR agonists [39] and Aβ induction of NFκB dependent genes requires TLR2, TLR4 and CD-14 [39], thus indicating that TLRs are important in sensing and responding to the presence of Aβ.…”
mentioning
confidence: 99%
See 1 more Smart Citation